DINAMIKA DAN PERAN PONDOK PESANTREN DALAM PENDIDIKAN ISLAM SEJAK ERA KOLONIALISME HINGGA MASA KINI - Ali Maulida (Sekolah Tinggi Agama Islam Al Hidayah, 2016)
In the history of Islamic education in Indonesia, pesantren has a very important role. The development of Islamic education that exist today can not be separated by the dynamic development of the pesantren world from the beginning of its history to the modern era with all its attending problems. Role is not only limited to the dissemination of knowledge and the propagation of Islam to various parts of the country, but also in building the spirit of resistance among Muslims against the invaders in the early days of its development . Pesantren has played a very important role in the history of the lives of Muslims and even the Indonesian people in general. Pesantren is not only a place to gain knowledge, and spreading Islamic proselytizing, but also a place to cultivate resistance to the colonial government of the Indonesian nation. Based on the statistical data presented, it appears that the boarding school has experienced a very significant development, both from the number of boarding schools as well as students who are learning. Data on the number of students by category and type of formal education that followed showed enough public awareness to get the full Islamic education including formal channels. In the education system that is applied by the institution of pesantren are many positive values that should be preserved and developed, such as; a heightened awareness that the process of learning as religious activities, the good relations between teachers (clerics, religious teacher) and student (students), pesantren as a place for science that is free from worldly purpose only, the values in the life of a dorm like, equation rights, putting an obligation rather than asking for the right, and so forth. On the other hand there are still many negative side of the process of education schools that must be addressed, including: the tendency of neglect life of the world, the attitude of fatalistic who disassociate ourselves without strong efforts in achieving the goal, absolute obedience to the teachers who tend to steer students to not think critically, and so forth. Keywords: pesantren, dakwah Islam, pendidikan Islam, kolonialisme.